2021
DOI: 10.1002/dc.24750
|View full text |Cite
|
Sign up to set email alerts
|

Utility of an immunocytochemical analysis for pan‐Trk in the cytodiagnosis of secretory carcinoma of the salivary gland

Abstract: Secretory carcinoma (SC) of the salivary gland is a rare distinct clinicopathological entity characterized by the presence of the ETV6‐NTRK3 fusion. Although the characteristic cytological features of SC have been recognized, its cytodiagnosis, especially differentiating SC from acinic cell carcinoma, is challenging. Recent studies have revealed that immunohistochemistry for pan‐tyrosine receptor kinase (Trk) and nuclear receptor subfamily 4 group member 3 (NR4A3) are specific for SC and acinic cell carcinoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…In this phase, 2 case reports 23,24 were excluded and finally, 13 articles were included for quantitative synthesis (Figure 1). 7,8,[12][13][14][15][16][17][18][19][20][21][22] 3.1 | Methodological characteristics of the studies Data extracted from all 13 studies including details on the country of origin, authors, total number, and histopathological type of SGTs and pattern of pan-TRK IHC manifestation are provided in Tables S1 & 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this phase, 2 case reports 23,24 were excluded and finally, 13 articles were included for quantitative synthesis (Figure 1). 7,8,[12][13][14][15][16][17][18][19][20][21][22] 3.1 | Methodological characteristics of the studies Data extracted from all 13 studies including details on the country of origin, authors, total number, and histopathological type of SGTs and pattern of pan-TRK IHC manifestation are provided in Tables S1 & 1.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were conducted between 2017 and 2022, in more than 5 different countries: 4 in the USA, 7,12-14 2 in France, 16,18 3 in Japan, 8,15,21 2 in China 19,20 1 in Taiwan, 22 and 1 was multicentric. 17 A total of 623 different SGTs including 255 SCs and 82 AciCCs were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Bell et al, 18 in a comparative study of pan‐TRK IHC on histological specimens, demonstrated sensitivity of 90.9% and specificity of 100%, indicating that it is a reasonable screening test. Ito et al 21 showed pan‐TRK nuclear staining on direct smears in all eight SC assessed by them, highlighting its utility in cytological diagnosis on conventional smears when cell blocks are not available or have sparse tumor cells. In the present case, pan‐TRK was immunopositive in the pleural metastases in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…Bell et al,18 in a comparative study of pan-TRK IHC on histological specimens, demonstrated sensitivity of 90.9% and specificity of 100%, indicating that it is a reasonable screening test. Ito et al21 showed pan-TRK nuclear staining on direct smears in all eight SC assessed by them, highlighting its utility in cytological diagnosis on conventional smears when cell blocks are not available or have sparse tumor cells.In the present case, pan-TRK was immunopositive in the pleural metastases in both cases. Thus, we report the detailed cytomorphological features of pleural metastasis from SC, showing that accurate diagnosis may not be possible on morphological characteristics alone, as they differ significantly from those on FNA, and resemble pleural metastases from anyF I G U R E 4 Pleural fluid from Case 2 shows loose clusters of tumor cells admixed with mesothelial cells and lymphocytes (A; MGG, 200Â).…”
mentioning
confidence: 99%
“…The expression of NTRK by immunocytochemistry has been previously described in secretory carcinoma of the salivary gland. 33 This tumour was previously named "mammary analogue secretory carcinoma" due to its resemblance to secretory breast carcinoma, including the ETV6-NTRK3 fusion. 34 SBC is associated with a favourable prognosis.…”
Section: Discussionmentioning
confidence: 99%